Associations of healthy eating index-2015 with osteoporosis and low bone mass density in postmenopausal women: a population-based study from NHANES 2007–2018 - Wang, Kai; Wu, Jinyi; Deng, Minggang; Tao, Fengxi; Li, Qingwen; Luo, Xin; Xia, Fang (Frontiers in Nutrition, 2024)
Purpose: The current study aimed to explore the associations of diet quality assessed by healthy eating index-2015 (HEI-2015) with risks of osteoporosis and low bone mineral density (BMD) among American postmenopausal women aged 50 years and older. Methods: Postmenopausal women aged 50 years and older in the National Health and Nutrition Examination Survey from 2007 through 2018 were included in the final sample. Analysis of variance and Rao-Scott adjusted chi-square tests were used to compare the characteristics across tertiles of HEI-2015. Univariate and multivariate weighted logistic regression models were employed to explore the associations of HEI-2015 tertiles and continuous HEI-2015 with the risks of osteoporosis and low BMD. Nonlinear dose-response associations were evaluated using weighted restricted cubic spline analyses, and the contributions of various HEI-2015 components were assessed using weighted quantile sum regression models. Results: The final sample included 3421 postmenopausal women aged 50 years and older representative for approximately 28.38 million non-institutionalized U.S. postmenopausal women. Osteoporosis prevalence decreased with HEI-2015 tertiles while the prevalence of low BMD showed no significant decrease. Compared with postmenopausal women in the first tertile of HEI-2015, those with the second (OR: 0.57, 95%CI: 0.38-0.84) and third (OR: 0.48, 95%CI: 0.29-0.78) HEI-2015 tertiles were associated with reduced osteoporosis risk after multivariate adjustments, but no significant association of HEI-2015 with the risk of BMD was identified. Furthermore, similar effects were confirmed in the sensitivity analyses and subgroup analyses and interaction effects. Moreover, significant nonlinear associations were observed between HEI-2015 with osteoporosis risk, and total vegetables, refined grains and greens and beans demonstrated the strongest protective effect among HEI-2015 components against osteoporosis.Conclusions: This study strongly suggests the significant negative associations of HEI-2015 with osteoporosis risk in American postmenopausal women. These findings highlight the importance of adherence to the dietary guidelines for Americans in reducing the risk of osteoporosis.